The Virtual Patient Simulator of Deep Brain Stimulation in the Obsessive Compulsive Disorder Based on Connectome and 7 Tesla MRI Data - Bonmassar, Giorgio (Cogn Int Conf Adv Cogn Technol Appl, 2014)
We present work in progress on the virtual patient model for patients with Deep Brain Stimulation (DBS) implants based on Connectome and 7 Tesla Magnetic Resonance Imaging (MRI) data. Virtual patients are realistic computerized models of patients that allow medical-device companies to test new products earlier, helping the devices get to market more quickly and cheaply according to the Food and Drug Administration. We envision that the proposed new virtual patient simulator will enable radio frequency power dosimetry on patients with the DBS implant undergoing MRI. Future patients with DBS implants may profit from the proposed virtual patient by allowing for a MRI investigation instead of more invasive Computed Tomography (CT) scans. The virtual patient will be flexible and morphable to relate to neurological and psychiatric conditions such as Obsessive Compulsive Disorder (OCD), which benefit from DBS.